Correction to “Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar” [Chem. Eng. J. 2026;538:176853. https://doi.org/10.1016/j.cej.2026.176853] - S. Al Azad; E. Kargaran; M. Saleknezhad; Y. Cheng; C. Quan; J. Chen; C. Sun; M. Madadi; F. Sun (Chemical Engineering Journal, 2026)

Commercial micro diets and weaning strategies influence immunity-related gene expression in bluefin bream (Sparidentax hasta) - I.S. Azad; S. El-Dakour; A.A. Al-Zalzalah (Animal Feed Science and Technology, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Impact of Tidal Phase on Inundation and Thrust Force Due to Storm Surge - A. S. M. Alauddin Al Azad; Kazi Samsunnahar Mita; Md. Wasif Zaman; Marin Akter; Tansir Zaman Asik; Anisul Haque; Mohammad Asad Hussain; Md. Munsur Rahman (Journal of Marine Science and Engineering, 2018)
Impact of storm surge largely varies depending on the tidal phase during the landfall of a tropical cyclone. This study investigates comparative variance in inundation condition and thrust force for an identical cyclone during low tide and high tide by applying a numerical model (Delft3D) and a semi-analytical model (DFM). A moderate strength cyclone, Mora, which made landfall on Bangladesh coast in May 2017 is selected to study its impact on land during low tide and high tide. Actual landfall time of Mora was during low tide. To study the impact of storm surge during high tide, a synthetic cyclone is created which has similar strength and track to that of Mora but makes landfall during high tide. The results show that inundation depth, inundation extent, and thrust force increase when a cyclone makes landfall during high tide compared to the condition when the cyclone makes landfall during low tide. But the relation between storm surge impact and tidal phase is not linear. It depends on the land topography of the location, direction of cyclone movement, direction and magnitude of water velocity and wind velocity, gradients of water surface and wind velocity, and proximity and position of the location with respect to cyclone track.